Study of determine effectiveness of a distance education programme as a method of continuing education in providing knowledge to institutional midwives in the Kalutara District in comparison Kurunegala District. - Fernando, T.E.I (My University, 1994)
This study was designed to assess the effectiveness of an experimental distance learning programme in a group of midwives in comparison with that of a in-service training programme held in the form of a workshop. The study group was selected from the midwives attached to peripheral medical institutions (from district hospital downward) of the deputy provincial director of health service area, Kalutara, while the control group was selected from the same type of institutions of the Kurunegala district.Pre-test and post-test marks, before and after the intervention were analyzed using student test and the paired student test. The analysis revealed that the base level knowledge of institutional midwives in both group was low and therefore there is the need for continuing education and both workshop method and distance learning method were equally effective in improving their knowledge significantly